CONTRIBUTION OF THE PHARMACEUTICAL INDUSTRY TO ECONOMIC GROWTH AND PUBLIC HEALTH IN INDONESIA: A LITERATURE REVIEW - Gunawan Widjaja; Diana Laila Ramatillah; Rio Johan Putra (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The pharmaceutical industry is one of the strategic sectors in economic development and health in Indonesia. As the fourth largest contributor among non-oil and gas manufacturing industries, the pharmaceutical industry has contributed significantly to economic growth, especially during the Covid-19 pandemic, where the sector's growth remained positive amid the national economic contraction. This contribution can be seen from the added value generated, increased investment, and job creation that continues to grow every year. In addition, the growth of the pharmaceutical industry in Indonesia is also influenced by an increase in population, an increase in life expectancy, and changes in people's behaviour that are increasingly aware of the importance of health. In terms of public health, the pharmaceutical industry plays an important role in providing quality, safe, and affordable medicines that support wider access to health services, including in government priority programmes such as the National Health Insurance (JKN). The availability of quality pharmaceutical products is also a key element in supporting the prevention and control of various diseases, as well as improving the quality of life and life expectancy of the Indonesian population. Innovation and technological adaptation carried out by the national pharmaceutical industry have helped drive production efficiency, expand the domestic market, and strengthen competitiveness at the regional level. However, the national pharmaceutical industry still faces major challenges, including dependence on imported raw materials, competition from global pharmaceutical products, production efficiency, and the need to strengthen sustainable research and development (R&D). Therefore, synergy between the government, industry players, and other stakeholders is needed to strengthen competitiveness and enlarge opportunities for the development of the pharmaceutical industry as a pillar of economic growth as well as improving public health in the future.